Effects of habbatus sauda (Nigella sativa) oil on sperm and testis parameters of nicotine treated rats / Ng Cho Ping - Ng, Cho Ping (2015)
Nicotine is considered as one of the most toxic substances that can be found in tobacco smoke. Besides being used as a natural insecticide, nicotine is pharmacologically active and has a negative impact on the reproductive system and fertility of males. In contrast, Nigella sativa seeds and oil have a lot of positive properties, such as antipyretic, analgesic, antihypertensive and antineoplastic. This study was carried out to investigate the potential protective effect of Nigella sativa (habbatus sauda) oil on nicotine treated male rat reproductive system. Forty-five Sprague-Dawley male rats (7-9 weeks old, 200-250g) were randomly divided into 5 groups; Nicotine (N) (0.5mg/100g), Nicotine Control (NC) (saline, 0.1ml/100g), habbatus sauda oil (HS) (6.0 휇 l/100g), habbatus sauda Control (HSC) (corn oil, 0.1ml/100g) and nicotine-habbatus sauda (NHS) (0.5mg/100g BW nicotine and 6.0 휇 l/100g habbatus sauda) groups and treated for 100 days. Sperm parameters, seminiferous tubules measurements, blood hormonal level and body weight increment were evaluated. Rats in NHS group (1.29±0.04 x 106sperm/ml) showed significantly higher sperm motility compared to N group (1.04±0.04 x 106sperm/ml). The HS group (90.69±0.01%) had the highest percentage of normal sperm followed by NHS (88.52±0.02%) and N (82.05±0.02%) groups (p<0.05). Percentage of live sperm for NHS group (95.96±0.01%) was significantly higher than N group (93.45±0.01%) but significantly lower than HS group (96.80±0.00%) (p<0.05). The NHS group showed significantly smaller diameter of seminiferous tubules (245.42±1.34μm) compared to N group (247.12±1.59μm) and HS group (249.95±1.37μm). Comparison on lumen diameter showed that N group had significantly wider lumen (100.74±1.75μm) compared to NHS (67.41±1.92μm) and HS (66.65±1.57μm) groups. Width of spermatogonia layer of NHS group (16.12±0.24μm) was significantly lower compared to HS (17.59±0.25μm) and N (19.51±0.29μm) groups. The NHS group (35.94±0.39μm) had significantly widest spermatocytes layer followed by HS (34.56±0.40μm) and N (32.56±0.41μm) groups (p<0.05). Both HS (38.05±0.61μm) and NHS (37.84±1.22μm) groups had significantly wider spermatid and sperm layer compared to N group (21.51±0.51μm). Treatments did not significantly affect blood hormonal level (testosterone, LH and FSH) and body weight increment pre and post treatment (p≥0.05). This study suggests that Nigella sativa (habbatus sauda) oil possessed protective effects against detrimental nicotinic effects on sperm quality and testis parameters of male rats.